2019
DOI: 10.18203/2320-6012.ijrms20191346
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of testicular lesions

Abstract: Background: Testis is affected by both neoplastic and non neoplastic conditions. Non neoplastic lesions of the testis include epididymo-orchitis, testicular atrophy, undescended testis, testicular abscess etc. Testicular tumors are relatively rare. They constitute the 4th most common cause of death from neoplasia in the young males. This study was undertaken to study the histopathological spectrum, age wise distribution and clinical symptoms of testicular lesions.Methods: This is a retrospective study of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(12 reference statements)
1
2
1
Order By: Relevance
“…In the present study we found 4 cases of Non-Hodgkin's lymphoma (15.38%) similar to previous studies by Sanjay M et al 2016 [11] and Deore K et al 2015 [3] but it was higher than previous studies by Takumalla et al 2019 [13] . Dhawle M et al 2019 [12] reported seminoma constituting 30.70% and malignant mixed germ cell tumor constituting 46% which is in close agreement with present study…”
Section: Distribution Of Tumors Of Testissupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study we found 4 cases of Non-Hodgkin's lymphoma (15.38%) similar to previous studies by Sanjay M et al 2016 [11] and Deore K et al 2015 [3] but it was higher than previous studies by Takumalla et al 2019 [13] . Dhawle M et al 2019 [12] reported seminoma constituting 30.70% and malignant mixed germ cell tumor constituting 46% which is in close agreement with present study…”
Section: Distribution Of Tumors Of Testissupporting
confidence: 92%
“…Manasi Sharma et al 2017 [7] reported 18.86% of cases of torsion. Dhawle M et al 2001 [12] reported 17.54% of cases of torsion. Fibrous pseudo tumor, spermatocele, orchitis with adrenal rest with spermatic cord represented 1 cases each (1.72%) Present study is comparable with the above studies.…”
Section: Distribution Of Tumor Like Lesionsmentioning
confidence: 96%
“…Unlike the present study, the most common age group, according to Dhawale et al [6], Sharma et al [3], and Baidya et al (2017) [7], was found to be 11-20 years (second decade). Most of the non-neoplastic lesions in this study contributed to the highest number of cases in the sixth decade.…”
Section: Discussioncontrasting
confidence: 81%
“…The undescended testis (present in the upper part of the scrotal sac) was the presenting complaint in 8.5% of cases. Studies done by Dhawale et al [ 6 ], Sharma et al [ 3 ], and Nwafor et al [ 8 ] reported the most common presentation to be scrotal swelling. Our study showed comparable results.…”
Section: Discussionmentioning
confidence: 99%